(untitled) (Verse Version, 2025)
The manifesto, distilled from the poetic practice and scholarly reflections within the Selected Poems of Ou Zhuang and centered on the spirit of Ou Hong’s “The Bastard Child of Poetry”, formally articulates the poetic principles and aspirations of the Lige School. Presented here as an appendix, it serves as both a conclusion to this section and an opening onto a broader poetic path, while also constituting a foundational theoretical document of the movement and being available as a standalone text for scholarly reference.